Analytical Solution for a Deep Tunnel Excavated in a Porous Elasto-Plastic Material Considering the Effects of Seepage Forces - R. E. Barbosa (Canadian Institute of Mining, Metallurgy and Petroleum, 2009)
Seepage forces generated during tunnel excavation affect the ground response and may cause severe instability problems, including total ground collapse and flooding into the tunnel. This paper presents a new closed-form analytical solution, for stresses and displacements around a cylindrical tunnel excavated in a porous water-bearing elasto-plastic material, which includes the effects of seepage forces. The analysis is carried out in terms of effective stresses and pore water pressures. The solution shows that seepage forces may have a major effect on the effective stresses around the tunnel, on the extent of the plastic zone, on the radial displacements, and on the tunnel support requirements. The conditions for development of a ?flowing ground? condition at the tunnel face have been identified. The paper presents a procedure for the hydromechanical ground-support interaction analysis, to determine the excavation induced inflow and the pressures acting on the lining, throughout the progressive driving of the tunnel, including the effective pressures exerted by the ground and the pressures generated by the water.